Photocatalytic degradation of perfluorooctane sulfonic acid and perfluorooctanoic acid using titanium dioxide/graphene oxide nanocomposite immobilized on polyvinyl alcohol film - Putthicha Boonchata; Narin Boontanon; Vinod Jindal; Humm Kham Zan Zan Aung; Chettiyappan Visvanathan; Shigeo Fujii; Suwanna Kitpati Boontanon (Case Studies in Chemical and Environmental Engineering)
In full-scale units, the real application of nanoparticles photocatalytic degradation is still challenging due to the requirement of post separation for recovery of fine particles. This work investigated the removal efficiencies of perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) using titanium dioxide (TiO2) nanoparticles coupling with graphene oxide (GO) sheets immobilized in polyvinyl alcohol (PVA) matrix via solution-casting and a heat-treatment process to achieve the TiO2/GO/PVA nanocomposite film as a photocatalyst. The operative parameters were focused on initial solution pH value, GO concentration, and heat-treatment time, which subsequently determined the optimal indices for the catalyst film. The structure characterization of the Ti–O–C bond indicated that a strong interaction between GO and TiO2 had been formed at the hydrolysis process while TiO2/GO nanoparticles were chemically embedded in PVA matrix by the heat-treatment method. The photocatalytic degradation of PFOS and PFOA produced a nanocomposite film with 25 wt% TiO2/GO that was treated at 120 °C for 3 h and exhibited a remarkable removal activity in acidic solution with a pH of 3. This condition efficiently degraded PFOS and PFOA by approximately 95.99 % and 96.89 %, respectively, through a photocatalytic reaction. This research presents a straightforward method to synthesize TiO2/GO/PVA catalyst that influences persistent organic pollutants (POPs) under ultraviolet irradiation, which is of practical significance for environmental applications.